Estudo estrutural, térmico e vibracional do crista de Bis (L-alaninato) de Níquel (II) di-hidratado - BALDEZ, Thays Silva (2016)
Amino acids complex of transition metals has increasingly attracted the interest of researchers due to their wide range of physical properties for understanding metal-amino acid interactions. In this work [Bis(L-Alaninato)Diaqua] Nickel(II) Dihydrate [Ni(C3H6O2N)2(H2O)2.2H2O] crystals were obtained by slow evaporation method using 0,1 mol/L of NiCl2.6H2O, 0,2 mol/L of L-alanine and NaOH. Rietveld refinement of X-ray data confirmed the structure. The structural properties of these crystals were studied by X-ray diffraction (XRD) in the temperature range from 25 to 150 °C. Thermal analysis experiments were performed by TG/DTA between 25 and 500 °C, and by DSC between 25 and 250 °C. The results obtained by TG/DTA indicate the loss of water molecules by [Bis(L-Alaninato)Diaqua] Nickel(II) Dihydrate crystals at temperatures of 64 and 117 °C, which was also confirmed by the results obtained by DSC. The X-ray diffraction pattern show new peaks, in temperatures around 55 and 110 ° C, indicating to loss of water by crystals. The transformation is irreversible because the diffraction pattern obtained after the sample return to the room temperature differs from that obtained before heating of the sample. The vibrational properties were analyzed by Raman spectroscopy between 25 and 185 °C. The Raman spectroscopy measurements as a function of the temperature show the loss of water molecules. The spectra at high temperatures resemble the spectrum at room temperature, showing that the crystal undergoes phase transformation, but probably do not change the crystal symmetry.